Synthesis of stereochemically-biased spiropyrans by microwave-promoted, one-pot alkylation–condensation. Issue 39 (27th September 2018) - Perry, Alexis; Davis, Kane; West, Lara
Abstract : Stereochemical control of spiropyran ring-closure was explored through synthesis of sterically-congested spiropyrans by a novel, efficient method. Abstract : A microwave-assisted, two-step, one-pot synthesis of spiropyrans has been developed. This process was used to synthesise a range of sterically-congested spiropyrans from readily available precursors, employing environmentally benign solvents. The unusual substituent pattern possessed by these structures has been shown to influence the stereoselectivity of spiropyran ring-closure.